Geotourism Based on Geoheritage as a Basis for the Sustainable Development of the Golija Nature Park, Southwest Serbia - Aleksandar S. Petrović; Ivana Carević; Dušica Trnavac Bogdanović; Marko Langović; Natalija Batoćanin; Jovan Petronijević (Land)
Golija Mountain, located in the southwestern part of Serbia, has been under protection as the Golija Nature Park since 2001. It is protected to preserve its forest ecosystems, diverse landscapes of exceptional beauty, and cultural heritage. Due to its natural and cultural values, the Golija Nature Park was declared a UNESCO Biosphere Reserve under the name “Golija-Studenica” in the same year. In addition to its ecosystem values, due to the complex geological and geomorphological past, there are a significant number of geodiversity objects on the mountains in the park. Research on these geodiversity objects has been the focus of the park’s administration in recent years. This protected natural area faces several challenges, with the sustainable development of tourism being one of the most significant. The construction of a large ski center is planned, which has already triggered the spontaneous development of unregulated weekend settlements near the mountain’s highest peaks. Geotourism provides an alternative to this development. Geosites, as the most representative landscapes and landforms, serve as key attractions for geotourists. The main goal of this work was to find appropriate geoactivities related to geosites that will enhance the geotourism offer, all with the aim of achieving the sustainable development of the Golija Nature Park.